2019
DOI: 10.1136/bmjsem-2019-000513
|View full text |Cite
|
Sign up to set email alerts
|

No pain no gain: a survey of use of healthcare and reasons not to seek healthcare by Norwegian climbers with chronic injuries

Abstract: ObjectivesTo assess the use of healthcare, and reasons not to seek healthcare, by climbers with a chronic injury.MethodRetrospective survey.SettingWeb-based questionnaire.Participants667 active climbers (385 with chronic injuries).Outcome measureUse of healthcare (including reasons not to seek healthcare if the patient was not attended by health professionals), performance level in sport climbing, onset of a climbing-related injury, site of injury, preferred style of climbing and gender differences.ResultOf th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…This, however, is not surprising, given the previously reported literature demonstrating high pain tolerance in climbers. 20,22,34 Synovitis of the ulnocarpal recess, as reported by Lutter et al, 38 was the most frequent diagnosis in our cohort. This was followed by ulnocarpal impaction, bone marrow edema, wrist sprains, and wrist ganglion cysts.…”
Section: Discussionsupporting
confidence: 80%
“…This, however, is not surprising, given the previously reported literature demonstrating high pain tolerance in climbers. 20,22,34 Synovitis of the ulnocarpal recess, as reported by Lutter et al, 38 was the most frequent diagnosis in our cohort. This was followed by ulnocarpal impaction, bone marrow edema, wrist sprains, and wrist ganglion cysts.…”
Section: Discussionsupporting
confidence: 80%
“…However, there were additional reported themes that were almost equally as common in injuries that were self-managed, including first, advice or reassurance being obtained from another person or self-research, and second, an unwillingness to seek medical care, such as having a belief that a medical practitioner could not do anything for the injury. Grønhaug et al 23 found similar themes in their study in which 24% of climbers reported a similar doubt about the knowledge of health professionals regarding climbing-related injuries, and 6% reported receiving help from a friend. However, our discovery that many climbers prefer self-research, often online, is a new observation.…”
Section: Discussionmentioning
confidence: 99%
“…Rock climbing, mountaineering, and indoor rock climbing are increasingly popular recreational activities in the United States, with over 6 million participants annually. [1][2][3] Climbing is increasingly accessible to the general population, and participants are transitioning from climbing indoors to climbing outdoors. 1 A range of injuries can occur while climbing, from falls to stressrelated musculoskeletal injuries.…”
Section: Introductionmentioning
confidence: 99%